2019
DOI: 10.21276/ijcmr.2019.6.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Lymphocyte Ratio (NLR) as a Bio Inflammatory Marker in Pre-eclampsia

Abstract: Introduction: Pre-eclampsia, a systemic disease unique to pregnancy, affects 3-14% of pregnant women. The aim of the present study was to evaluate Neutrophil Lymphocyte Ratio (NLR) as a bio inflammatory marker of pre-eclampsia (PE), a hypertensive disorder of pregnancy characterized by hypertension and proteinuria after 20 weeks of gestation. Material and Methods: This case control study was carried out over a period of 10 months after informed consent and ethical clearance. The study population included 70 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In women with preeclampsia, neutrophils are activated in the placental circulation under hypoxic conditions which contribute to increased vascular resistance in preeclampsia. 15 Neutrophilto-lymphocyte ratio in preeclamptic patients was significantly higher compared to those without preeclampsia. 15 Preeclampsia is characterized by antiangiogenetic and inflammation, thus increasing in proinflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), which ultimately causes the expression of the acute phase protein CRP.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In women with preeclampsia, neutrophils are activated in the placental circulation under hypoxic conditions which contribute to increased vascular resistance in preeclampsia. 15 Neutrophilto-lymphocyte ratio in preeclamptic patients was significantly higher compared to those without preeclampsia. 15 Preeclampsia is characterized by antiangiogenetic and inflammation, thus increasing in proinflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), which ultimately causes the expression of the acute phase protein CRP.…”
mentioning
confidence: 84%
“…15 Neutrophilto-lymphocyte ratio in preeclamptic patients was significantly higher compared to those without preeclampsia. 15 Preeclampsia is characterized by antiangiogenetic and inflammation, thus increasing in proinflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), which ultimately causes the expression of the acute phase protein CRP. 16 In preeclampsia, there is also an increase in procalcitonin, which is associated with systemic inflammation, and increases in other proinflammatory cytokines and cytotoxic activity on hepatocytes and endothelium.…”
mentioning
confidence: 84%
“…Therefore, the NLR is considered as a provider of diagnostic and prognostic value in preeclampsia. [18][19][20][21][22] Mannaerts et al 10 reported that patients with preeclampsia have NLR value higher than normotensive pregnancies, although it is not significantly different. In contrast, some studies reported that the NLR value of patients with preeclampsia is significantly different compare with normotensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…19 The cut-off value for NLR in predicting preeclampsia have been proposed by some authors. Singhal et al 20 found that the NLR has a cutt-off value of ≥ 4.86 with a sensitivity of 68.6% and a specificity of 80.0% in predicting preeclampsia. Prasetyo et al 22 found that the NLR is associated with preeclampsia with cut-off values between 3.5-5.6 in different sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation